Hierarchical assembly involving hydroxyethyl-substituted imidazolium cations and p-sulfonatocalix[4]arenes - Ling, I.; Alias, Y.; Skelton, B.W.; Raston, C.L. (CSIRO Publishing, 2010)
A multiple-component bilayer involving four different ions has preferential binding of functionalized 3-(2-hydroxyethyl)-1-methylimidazolium in the cavity of bowl-shaped p-sulfonatocalix[4]arene, with the supermolecule being capped by a water molecule involving an O-H center dot center dot center dot pi(imidazolium) interaction, an O center dot center dot center dot HO H-bond involving the hydroxyethyl group, and an SO center dot center dot center dot HO H-bond. The nature of the interplay of the components has been mapped out using Hirshfeld surface analysis. The [imidazolium boolean AND calixarene] supermolecule persists in solution.